2005
DOI: 10.1177/0897190005278510
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects Associated With Antiretroviral Therapy and Potential Management Strategies

Abstract: A variety of adverse drug reactions (ADRs) affecting many organ systems may be observed with antiretroviral therapy (ARV), and they can be differentiated into short- and long- term effects, class effects, or individual drug effects. Commonly seen ADRs include dermatological reactions, associated with nonnucleoside reverse transcriptase inhibitors (NNRTIs) and some protease inhibitors (PIs), and gastrointestinal problems, a major side effect of PIs and of some nucleoside reverse transcriptase inhibitors (NRTIs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 85 publications
0
11
1
Order By: Relevance
“…Zidovudine has been implicated as the most common cause of hematological toxicity (14,25,26). However, no association between regimens containing zidovudine and haematological disorders was found in our study, perhaps because the number of patients was too small.…”
Section: Discussioncontrasting
confidence: 55%
“…Zidovudine has been implicated as the most common cause of hematological toxicity (14,25,26). However, no association between regimens containing zidovudine and haematological disorders was found in our study, perhaps because the number of patients was too small.…”
Section: Discussioncontrasting
confidence: 55%
“…ADRs such as nausea reduce food intake and, subsequently, a gain in BMI. In addition, patients who took zidovudine-containing regimens, as reported elsewhere [26], as well as the unemployed, were more likely to develop severe ADRs in this sample. Studies in sub-Saharan patients [42], including our previous study [32], reported that eating insufficient food, which is more likely related with unemployment, exacerbated ADRs with ART.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies had also reported NRTIs as a risk factor for the occurrence of gastrointestinal problems [26]. The overall prevalence of gastrointestinal complaints (54.5 %) was lower than reported in a cohort of Iranian patients (67.3 %), where 81 % of patients were taking a zidovudine-based regimen [24].…”
Section: Discussionmentioning
confidence: 92%
“…Hepatic toxicity occurs in about one-third (1/3) of HIV-infected patients after initiation of therapy [8]. Metabolic complications are frequently reported, such as lipodystrophy, hyperinsulinemia/hyperglycemia and osteoporosis, osteonecrosis associated with Protease Inhibitors (PIs), and lactic acidosis with Nucleoside Reverse Transcriptase Inhibitors (NRTI) [7,9]. Dyslipidemia associated with an increased risk of cardiovascular disease is also reported in HIV-1 infected patients who receive ARV [10].…”
Section: Introductionmentioning
confidence: 99%
“…These adverse effects result in changes in biological parameters with often clinical manifestations [6], which can affect many organs of the body. The most common adverse reactions are dermatological reactions and Gastrointestinal (GI) disorders [7]. Hepatic toxicity occurs in about one-third (1/3) of HIV-infected patients after initiation of therapy [8].…”
Section: Introductionmentioning
confidence: 99%